Isotretinoin and Psychiatric Effects - Zennure Takci; AyseSerap Karadag; Hatice Burakgazi Yilmaz (European Medical Journal, 2014)
Isotretinoin is a vitamin A derivative that has been commonly used by dermatologists for the treatment of acne. Isotretinoin has many dose-related side-effects, which have caused many debates lately, especially related to psychiatric and gastrointestinal issues. Since the introduction of isotretinoin into the market, there have been a growing number of reported cases of psychiatric side-effects, including: depression, suicide, aggression, psychosis, mood swings, violent behaviour, hostility, bipolar disorder, and obsessive compulsive disorder. According to some animal studies, isotretinoin can pass the blood-brain barrier and it may cause serious side-effects. On the other hand, it has been shown that isotretinoin can decrease the psychiatric symptoms of many psychiatric patients. Because a definitive causal relationship has not been established, it remains unclear as to whether isotretinoin therapy leads to psychopathology. In this review article, we evaluate the published articles about the psychiatric side-effects of isotretinoin and discuss the psychopathologic effects of isotretinoin.